Effect of exogenous emulsifier supplementation on growth performance, and nutrient digestibility in broiler chickens - Lee, Chia Yin (2015)
Digestion and absorption of fat in young chicks are not efficient because of a low level of natural lipase production. Therefore an experiment was conducted to study the effect of exogenous emulsifier (glycerol polyethylene glycol recinoleate) supplementation on growth performance and nutrient digestibility in broiler chickens. A total of 120 one-day-old male Cobb broilers were assigned in groups of 10 to 12 battery cages. The chicks were randomly assigned to two dietary treatments, with 6 replicate cages per treatment. The diets were either standard broiler starter (2972 kcal ME/kg and 21.002% CP) and standard broiler finisher (3167 kcal ME/kg and 18.068% CP) (OC) or similar diets + 0.05% Volamel (OV). Volamel is a commercial exogenous emulsifier manufactured by Nukamel Inc., Hoogbuul, Olen, Belgium. Weekly body weight, feed intake and feed conversion ratios (FCR) were recorded. Energy and fat digestibilities were determined on day 7 and 14. Diet had no significant effect on body weight, feed intake, and FCR throughout the period of study. Fat digestibility was not affected by diet but birds supplemented with Volamel had lower energy digestibility on both day 7 and 14. The lack of beneficial effects of emulsifier supplementation could be associated with the type of emulsifier used, type of dietary fat and level of free fatty acids found in feed prepared. In conclusion, the results of this experiment showed that supplementation of exogenous emulsifier had no significant effect on both growth performance and nutrient digestibility in broiler chickens. Further studies on the effect on type and level of dietary fat on the action on exogenous emulsifier are necessary for better improvement in the efficiency of broiler chicken production.